Cacao: The Treasure Of The Amazon - De la Fuente de Diez Canseco, Luciana (2018)
The world would not be as it is today without the Amazonia. It is home to the largest area of tropical rainforest where more than half of our planet’s animal, plant and insect species live. This immense green ocean plays a vital role in the regulation of the Earth’s climate, the purification of water, and the absorption of carbon. Peru is a country blessed by nature. Its largest and most biodiverse region is the Amazonia. According to the National Ministry of the Environment, the Amazonia covers, in its entirety, the departments of Loreto, Ucayali, and Madre de Dios; almost entirely, the departments of San Martín and Amazonas; very partially, the departments of Pasco, Junín, Huánuco and Cusco; and, finally, certain protected areas of Cajamarca, Puno and Ayacucho.